2003
DOI: 10.3141/1830-08
|View full text |Cite
|
Sign up to set email alerts
|

Safety Effects of Differential Speed Limits on Rural Interstate Highways

Abstract: To compare the safety effects of a uniform speed limit (USL) for all vehicles and a differential speed limit (DSL) for cars and heavy trucks, crash, speed, and volume data for rural Interstate highways for the period 1991 through 2000 were obtained from nine states. These states were divided into four policy groups based on the type of speed limit employed during the period: maintenance of a uniform limit only, maintenance of a differential limit only, a change from a uniform to a differential limit, and a cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…In 2005, Garber et al compared crash, traffic volumes, vehicles speeds, and other data for Virginia, which had transitioned from a DSL policy to a USL policy, and three other groups: (a) states that were transitioning from USL to DSL, (b) states that were maintaining USLs, and (c) states that were maintaining DSL (40). The results showed differences between passenger vehicle and truck speeds but no consistent safety differences.…”
Section: Dsls Versus Usls For Trucks and Busesmentioning
confidence: 99%
“…In 2005, Garber et al compared crash, traffic volumes, vehicles speeds, and other data for Virginia, which had transitioned from a DSL policy to a USL policy, and three other groups: (a) states that were transitioning from USL to DSL, (b) states that were maintaining USLs, and (c) states that were maintaining DSL (40). The results showed differences between passenger vehicle and truck speeds but no consistent safety differences.…”
Section: Dsls Versus Usls For Trucks and Busesmentioning
confidence: 99%
“…DSLs for trucks and cars are becoming a promising way to enhance highway operation and safety. Thus, in this study we focus on DSL strategy which restricts vehicles with specific size and weight, to travel at lower speeds than the rest of the traffic stream [ 42 ], as heavier vehicles require a larger stopping distance and stopping time than do passenger cars [ 43 ]. Thereby, vehicles are divided into three types based upon their capacities.…”
Section: Intelligent Advisory Speed Limit Dedication (Iasld)mentioning
confidence: 99%
“…Wilmot and Khanal (1999) documented the effect of speed limits on vehicle speed and safety on roadways and concluded that there was no evidence of a positive impact of differential speed limits on highway safety. A report, by Garber, Miller, Yuan, and Sun (2003), compared the safety effects of differential speed limits on rural interstate highways to those with uniform speed limits. In this work it was found that changing from a uniform speed limit to a differential speed limit or vice versa had no impact on the mean speed and speed variance.…”
Section: Differential Speed Limitsmentioning
confidence: 98%